The effects of Nd2O3 concentration in the laser emission of TeO2-ZnO glasses - Moreira, L. M.; Anjos, V.; Bell, M. J.V.; Ramos, C. A.R. [UNESP]; Kassab, L. R.P. [UNESP]; Doualan, D. J.L.; Camy, P.; Moncorgé, R. (Elsevier, 2016)
The present work reports the modification introduced by different Nd2O3 concentration on optical properties and the laser operation of Nd3+ doped (TeO2-ZnO) bulk tellurite glass. The spectroscopic data are analyzed within the Judd Ofelt formalism framework and the results are compared to the fluorescence lifetime and emission measurements to derive values for the quantum efficiency and the stimulated emission cross section of the considered 4F3/2 → 4I11/2 infrared laser transition around 1062.5 nm. Continuous-wave laser action is achieved with this bulk tellurite glass by pumping the sample inside a standard plan-concave mirror laser cavity with different output couplers. It is possible to observe coherent emission only for the lower concentration (0.5%(wt.) of Nd2 O3). Also laser action could only be observed for this sample with threshold pump power of 73 mW associated with a laser slope efficiency of 8% for an output coupler transmission of 4% indicating that TeO2-ZnO are potential materials for laser action. The results presented in this work together with those previously reported with higher concentration (1.0% (wt) of Nd2O3) determine the adequate Nd2O3 concentration for laser action and guide the correct experimental procedure for TeO2-ZnO glasses preparation.
Keywords: Glasses; Laser; Neodymium; Tellurite